The Analysis of Fixed Asset Balance preparing process in Management of Regional Assets at OPD BPKAD Banten Province - Resky Jonathan Pratama Tobing (PT Larva Wijaya Penerbit, 2022)
The study aim is to analysis of fixed asset balance preparing process in management of regional assets at local government finance and assets (OPD BPKAD Banten Province). The analysis used descriptive analysis method by collecting and filtering the data/information obtained thoroughly and in detail, then described in order to obtain a clear picture of the process of preparing the fixed asset balance at the OPD BPKAD Banten Province. Based on observations during the internship process, the results of this study is obtained in the form of the process of preparing a fixed asset balance which is then seen for compliance with Government Regulation Number 27 of 2014 concerning Management of State/Regional Property, Regulation of the Minister of Home Affairs Number 19 of 2016. The process of preparing the Fixed Asset Balance in the Management of Regional Assets at the OPD BPKAD Banten Province went well because it reconciled quickly and precisely. The use of the ATISISBADA application that makes it easy to quickly enter the value of goods so that data collection is more optimal